2019
DOI: 10.1186/s12903-019-0854-x
|View full text |Cite
|
Sign up to set email alerts
|

Gelatinolytic activity in gingival crevicular fluid and saliva of growing patients with Marfan syndrome: a case-control study

Abstract: Background Aim of the study was to evaluate the gelatinolytic activity in the saliva and gingival crevicular fluid from a sample group of subjects with Marfan syndrome. Methods Two groups were analyzed in this case-control study. A group of 28 subjects with Marfan syndrome (MG) was recruited from the Centre for Rare Disease, Marfan Clinic of Tor Vergata University Hospital. The second sample, 23 subjects, with the same characteristics and without any syndrome, was the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Besides, fibrillin-1 has been suggested to be essential for normal tissue structure and gene expression of the periodontal ligament [ 30 ]. What is more, a recent study revealed higher MMP-13 activity in the crevicular fluid of MFS patients compared to healthy individuals, which could lead to significant degradation of the periodontal matrix and an altered response in case of periodontal inflammation [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, fibrillin-1 has been suggested to be essential for normal tissue structure and gene expression of the periodontal ligament [ 30 ]. What is more, a recent study revealed higher MMP-13 activity in the crevicular fluid of MFS patients compared to healthy individuals, which could lead to significant degradation of the periodontal matrix and an altered response in case of periodontal inflammation [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gelatin substrate zymography was used for the evaluation of saliva MMP gelatinolytic activities in the salivary samples [ 16 ]. Briefly, 1.8 μg of saliva proteome were loaded in each lane.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 [8,9,[17][18][19][20][21][22][23][24] lists the most important aspects of the studies that were considered. Peer-reviewed journals were used to publish all of the investigations.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Peer-reviewed journals were used to publish all of the investigations. A total of 3 of the 10 studies were carried out in Germany [8,17,20] and Italy [18,19,21], 2 in Japan [22,23], and 2 in Belgium [9,24]. The measurement of gingival and periodontal clinical parameters was the most employed method in the studies.…”
Section: Study Characteristicsmentioning
confidence: 99%